The N-terminal peptide moiety of the Mycobacterium tuberculosis 19 kDa lipoprotein harbors RP105-agonistic properties. Issue 2 (9th January 2018) - Schultz, Thomas E; Wiesmüller, Karl-Heinz; Lucas, Megan; Dobos, Karen M; Baxter, Alan G; Blumenthal, Antje
Abstract: Radioprotective 105 kDa (RP105, CD180) is a member of the Toll-like receptor (TLR) family that interacts with TLR2 and facilitates recognition of mature lipoproteins expressed by Mycobacterium tuberculosis and Mycobacterium bovis BCG. In this study, we used synthetic lipopeptide analogs of the M. tuberculosis 19 kDa lipoprotein to define structural characteristics that promote RP105-mediated host cell responses. A tripalmitoylated lipopeptide composed of the first 16 N-terminal amino acids of the M. tuberculosis 19 kDa lipoprotein induced RP105-dependent TNF and IL-6 production by macrophages. Di- and tripalmitoylated variants of this lipopeptide elicited an equivalent RP105-dependent response, indicating that while the lipid moiety is required for macrophage activation, it is not a determinant of RP105 dependency. Instead, substitution of two polar threonine residues at positions 7 and 8 with nonpolar alanine residues resulted in reduced RP105 dependency. These results strongly suggest that the amino acid composition of the M. tuberculosis 19 kDa lipoprotein, and likely other mycobacterial lipoproteins, is a key determinant of RP105 agonism.